Web Development with Django - Shaw, Ben; Badhwar, Saurabh; Bird, Andrew; Bhushan, S. Bharath, 1990-; Guest, Chris (Packt Publishing, 2021)
Learn how to create your own websites simply, safely, and quickly with Django by tackling practical activities based on realistic case studies Key Features Understand Django functionality and the Model-View-Template (MVT) paradigm Create and iteratively build a book review website, adding features as you build your knowledge Explore advanced concepts such as REST API implementation and third-party module integration Book Description Do you want to develop reliable and secure applications which stand out from the crowd, rather than spending hours on boilerplate code? Then the Django framework is where you should begin. Often referred to as a 'batteries included' web development framework, Django comes with all the core features needed to build a standalone application. Web Development with Django takes this philosophy and equips you with the knowledge and confidence to build real-world applications using Python. Starting with the essential concepts of Django, you'll cover its major features by building a website called Bookr - a repository for book reviews. This end-to-end case study is split into a series of bitesize projects that are presented as exercises and activities, allowing you to challenge yourself in an enjoyable and attainable way. As you progress, you'll learn various practical skills, including how to serve static files to add CSS, JavaScript, and images to your application, how to implement forms to accept user input, and how to manage sessions to ensure a reliable user experience. Throughout this book, you'll cover key daily tasks that are part of the development cycle of a real-world web application. By the end of this book, you'll have the skills and confidence to creatively tackle your own ambitious projects with Django. What you will learn Create a new application and add models to describe your data Use views and templates to control behavior and appearance Implement access control through authentication and permissions Develop practical web forms to add features such as file uploads Develop a RESTful API and JavaScript code that communicates with it Connect to a database such as PostgreSQL Who this book is for Web Development with Django is designed for programmers who want to gain web development skills with the Django framework. To fully understand the concepts explained in this book, you must have basic knowledge of Python programming, as well as familiarity with JavaScript, HTML, and CSS.